Sistem Informasi Pencarian Kost di Kabupaten Manokwari Berbasis Web Menggunakan Framework Laravel dan Bootstrap: Web-Based Boarding House Search Information System in Manokwari Regency Using The Laravel Framework and Bootstrap - Anastasia Sarkol; Josua Josen A. Limbong (JISTECH: Journal of Information Science and Technology, 2025)
Manual boarding house searches are often a challenge for the community due to limited information, distance, and time. This study designed and developed a web-based boarding house search information system called Kos Logik, intended for the Manokwari Regency area. The system was built using the Laravel framework as the backend, Bootstrap for the frontend, MySQL as the database, and the Waterfall development method, which includes requirements analysis, design, implementation, testing, and maintenance. The application involves three types of users: boarding house seekers, boarding house owners, and administrators. The main features include registration, login, location-based search, room details, favorites storage, booking, and reviews. Boarding house owners can add room data, manage facilities, monitor booking status, and view tenant data. Testing using the black box method showed that all features worked as expected. The results of this study are expected to provide an efficient and effective solution for searching and managing boarding houses in Manokwari Regency.